Aqueous-phase detection of antibiotics and nitroaromatic explosives by an alkali-resistant Zn-MOF directed by an ionic liquid. Issue 3 (8th January 2020) - Qin, Jian-Hua; Huang, Ya-Dan; Shi, Ming-Yu; Wang, Hua-Rui; Han, Min-Le; Yang, Xiao-Gang; Li, Fei-Fei; Ma, Lu-Fang
Abstract : An alkali-resistant 3D anionic Zn-MOF directed by [BMI]Br ionic liquid has been synthesized for aqueous-phase detection of antibiotics and nitroaromatic explosives. Abstract : An alkali-resistant Zn-MOF directed by [BMI]Br ionic liquid, (BMI)2 [Zn3 (ptptc)2 ] (1 ), based on a π-electron-rich terphenyl-tetracarboxylic acid, has been synthesized under the combination of hydro/solvothermal and ionothermal condition (BMI = 1-butyl-3-methylimidazolium, H4 ptptc = p -terphenyl-3, 3′′, 5, 5′′-tetracarboxylic acid). In 1, the trinuclear Zn(ii ) clusters are linked by the organic moieties of the ptptc ligands, resulting in a 3D anionic framework structure with highly disordered [BMI] + cations filled in the pores. 1 exhibits good chemical stability in water and NaOH solutions (pH range of 7–12), which allow it to detect antibiotics and nitroaromatic explosives in an aquatic system. 1 represents high fluorescence quenching efficiency toward NFs (furazolidone, FZD; nitrofurazone, NZF; nitrofurantoin, NFT), NMs (ronidazole, RDZ; metronidazole, MDZ; dimetridazole, DTZ; ornidazole, ODZ) and nitrophenol (2-nitrophenol, 2-NP; 3-nitrophenol, 3-NP; 4-nitrophenol, 4-NP; 2, 4, 6-trinitrophenol, TNP) in water solution, respectively.